Evaluation Of The Influence Of Traffic Lights on Traffic Comfort And Safety Users: Case Study of Cigasong Roundabout, Majalengka City - Iip Faturohman; Mohamad Taufik; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2025)
Recognizing traffic lights is an essential technological advancement. element for automated driving in urban areas. Traffic signs are one of the essential elements in the transportation system that regulate, warn, and provide information to road users. Traffic signs are designed to improve safety, efficiency, and convenience in driving. The purpose of this investigation is to find the one lack influence of movement signs traffic comfort and safety and see the impact on motorists; traffic lights reduce accidents. This study is located at the Cigasong roundabout. The research study employs a qualitative methodology. with perception analysis. Parameters are respondents' perceptions of the level of importance and satisfaction with traffic light signs on the road, using a scale of 1 to 5 from not crucial to important and dissatisfied to satisfied. The data was processed using the Importance Performance Analysis (IPA) method. The data collected from 25 respondents were divided by age, gender, and the vehicle used when crossing the Cigasong roundabout. From the questionnaire results, the majority of the age range that has passed through the Cigasong roundabout is less than 20 years and 21 to 30 years, and the least frequent passing through the Cigasong roundabout is age 41 to 50. While the majority of the gender that has passed through the Cigasong roundabout is male. Most road users who have passed through the Cigasong roundabout use motorbikes, and the least frequently use cars.